1973
DOI: 10.1113/jphysiol.1973.sp010097
|View full text |Cite
|
Sign up to set email alerts
|

The effect of some molecules and ions on gastric function in the milk‐fed calf

Abstract: 1. The abomasum of the milk‐fed calf has been examined using an adaptation of the Serial Test Meal method devised by Hunt & Spurrell (1951). The emptying process, acid secretion and pepsin secretion were studied. 2. Using serial test meals of simple solutions instilled into the abomasum via a cannula, our investigation leaves no doubt that the osmolarity of the abomasal contents significantly modifies the rate of abomasal emptying. 3. Hypotonic and isotonic solutions of sodium chloride and sodium bicarbonate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
1

Year Published

1975
1975
1990
1990

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 13 publications
6
22
1
Order By: Relevance
“…At the points where no titratable acid is delivered to the duodenum -that is water, and isotonic saline at pH 50-70 -a difference of 20 o in gastric emptying occurs. This effectiveness of both NaCl and NaHCO3 in eliciting gastric emptying compared with water has been noted previously F. R. BELL, M. NOURJ AND D. E. WEBBER (Hunt, 1956;Hunt & Knox, 1969;Bell & Razig, 1973b). It is also apparent from Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…At the points where no titratable acid is delivered to the duodenum -that is water, and isotonic saline at pH 50-70 -a difference of 20 o in gastric emptying occurs. This effectiveness of both NaCl and NaHCO3 in eliciting gastric emptying compared with water has been noted previously F. R. BELL, M. NOURJ AND D. E. WEBBER (Hunt, 1956;Hunt & Knox, 1969;Bell & Razig, 1973b). It is also apparent from Fig.…”
Section: Discussionsupporting
confidence: 83%
“…In man (Hunt & Knox, 1969) and the calf (Bell & Razig, 1973b), as the concentration of HCl in a meal increases so emptying of the stomach decreases. In contrast to the inhibitory effect of duodenal acidification, alkalinization by isotonic NaHCO3 is an effective stimulant of gastric emptying and secretion (Bell & Webber, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Hunt (1956) had suggested that this feed-back control mechanism from the duodenum to the gastric musculature was initiated by the action of components of the gastric chyme on an osmoreceptor situated in the duodenum. Bell & Razig (1973b) corroborated this suggestion by showing experimentally that a similar mechanism probably operated between the duodenum and stomach of the milk-fed calf.…”
Section: Introductionsupporting
confidence: 53%
“…), since this molecule is known to activate abomasal emptying at this concentration, and HCl (60 m-equivfl. ), which is strongly inhibitory, together with distilled water as control infusate (Bell & Razig, 1973b).…”
Section: Methodsmentioning
confidence: 99%
“…In addition two calves (nos. 9 and 10) were provided with antral-duodenal re-entrant cannulae (Bell & Mostaghni, 1975 NaHCO3 (300 m-osmole/kg) was added to the majority of meals to stimulate abomasal emptying and on four occasions HCl (0-06 M) (Bell & Razig, 1973b).…”
Section: Abomnal Cannulationmentioning
confidence: 99%